Molecular mechanisms of heptaplatin effective against cisplatin-resistant cancer cell lines: less involvement of metallothionein - Choi, Cheol-Hee (BioMed Central, 2004)
BACKGROUND: Heptaplatin is a new platinum derivative with anticancer activity against various cancer cell lines, including cisplatin-resistant cancer cell lines (Cancer Chemother Pharmacol 1995; 35: 441). METHODS: Molecular mechanisms of heptaplatin effective against cisplatin-resistant cancer cell lines has been investigated in connection with metallothionein (MT). Cytotoxicity was determined by an MTT assay. MT mRNA, was determined by RT-PCR assay. Transfection study was carried out to examine the function of MT. RESULTS: Of various gastric cancer cell lines, SNU-638 and SNU-601 showed the highest and lowest levels of MT mRNA, respectively, showing 80-fold difference. The IC(50 )values of SNU-638 to cisplatin, carboplatin and heptaplatin were 11.2-fold, 5.1-fold and 2.0-fold greater than those of SNU-601, respectively. Heptaplatin was more effective against cisplatin-resistant and MT-transfected gastric cancer sublines than cisplatin or carboplatin was. In addition, heptaplatin attenuated cadmium, but not zinc, induction of MT. CONCLUSION: These results indicate that molecular mechanisms of heptaplatin effective against cisplatin-resistant gastric cancer sublines is at least in part due to the less involvement of MT in heptaplatin resistance as well as its attenuation of MT induction.